2018
DOI: 10.1002/chem.201801871
|View full text |Cite
|
Sign up to set email alerts
|

Reversible C−H Activation, Facile C−B/B−H Metathesis and Apparent Hydroboration Catalysis by a Dimethylxanthene‐Based Frustrated Lewis Pair

Abstract: Ad imethylxanthene-based phosphine/borane frustrated Lewis pair (FLP) is shown to effect reversible CÀH activation, cleaving phenylacetylene, PhCCH, to give an equilibrium mixture of the free FLP and phosphoniuma cetylide in CD 2 Cl 2 solution at room temperature. This systema lso reacts with BÀHb onds although in ad ifferentf ashion:r eactions with HBpin and HBcatp roceed via CÀB/BÀHm etathe-sis, leading to replacement of the -B(C 6 F 5 ) 2 Lewis acid component by -Bpin/-Bcat, and transfer of HB(C 6 F 5 ) 2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 66 publications
4
20
0
Order By: Relevance
“…B(C 6 F 5 ) 3 is by far the most widely used acid component in FLPs, enabling the synergistic activation of small molecules and unsaturated bonds . Stephan and Erker, reported the reactivity of alkynes towards B(C 6 F 5 ) 3 /phosphine FLPs, which result in the apparent trapping of the σ‐adduct I by the Lewis base …”
Section: Methodsmentioning
confidence: 99%
“…B(C 6 F 5 ) 3 is by far the most widely used acid component in FLPs, enabling the synergistic activation of small molecules and unsaturated bonds . Stephan and Erker, reported the reactivity of alkynes towards B(C 6 F 5 ) 3 /phosphine FLPs, which result in the apparent trapping of the σ‐adduct I by the Lewis base …”
Section: Methodsmentioning
confidence: 99%
“…Reactions of 114 with pinacolborane (HBpin) and catecholborane (HBCat) induces boryl exchange at the xanthene backbone via B-C/B-H σ-bond metathesis, and the released Piers' borane HB(C6F5)2 is trapped by the P centre as a classic Lewis adduct (Scheme 33). 80 The resulting derivatives 120 and 121 have been spectroscopically and crystallopgraphically characterized. They display two sets of 11 In line with the reactivity of xanthene-bridged P-B derivatives described thus far, Vasko, Kamer, Aldridge et al reported the ability of 113 and 114 to activate C(sp)-H bonds.…”
Section: Scheme 31 (Reversible) Activation Of H2 By 112-114mentioning
confidence: 99%
“…They display two sets of 11 In line with the reactivity of xanthene-bridged P-B derivatives described thus far, Vasko, Kamer, Aldridge et al reported the ability of 113 and 114 to activate C(sp)-H bonds. 80 Derivatives 113 and 114 react with phenylacetylene (PhCCH) to provide the corresponding phosphonium alkynylborates 124 and 125, respectively (Scheme 34). Interestingly, the C(sp)-H activation is reversible with the PPh2 compound 114 (solutions of 125 show signals related to 114 and free PhCCH), but not with 113 featuring a more basic PMes2 moiety.…”
Section: Scheme 31 (Reversible) Activation Of H2 By 112-114mentioning
confidence: 99%
“…4 Recently we also showed that FLP 1a reacts readily with the C-H bonds in terminal alkynes and with the B-H bonds in selected boranes, and can act as a pre-catalyst for the hydroboration of alkynes. 5 In terms of other E-H bonds, the interactions of FLPs with water and O-H containing systems are important, [6][7][8][9][10][11][12][13] not least because they influence strongly their sensitivity to trace impurities present in commercial substrates and solvents; as a consequence, it is often necessary to carry out catalytic processes under the exclusion of moisture. Similar chemistry potentially arises when using alcohol solutions in combination with FLPs as alcohols can have comparable nucleophilicity/basicity to H 2 O.…”
mentioning
confidence: 99%
“…The boron centre in each adduct gives rise to a broad signal in the 11 B{ 1 H} spectrum in the range characteristic of four-coordinate boron species (δ B = 4.5 (2), 5.4 (3), and 3.7 ppm (4)), consistent with the solid state structures. 5 Earlier literature reports detailing the reactivity of FLPs towards water favour heterolytic O-H bond cleavage; [6][7][8][9][10][11] for example the t Bu 3 P/B(C 6 F 5 ) 3 system is reported to activate one molecule of H 2 O to give the phosphonium borate…”
mentioning
confidence: 99%